(untitled) (Global Journal of Human-Social Science, 2022)
The study seeks to assess an important question that needs to be asked How can we get a clearer picture of the socio-cultural history of the Yao than that that exists in general among Yaos themselves as well as people who oppose the Yao This is a very large topic and this study will only start to trace some of the important historical facts and perceptions